Application of non-starter lactic acid bacteria as biopreservative agents to control fungal spoilage of fresh cheese. (May 2016) - Sedaghat, Hossein; Eskandari, Mohammad Hadi; Moosavi-Nasab, Marzieh; Shekarforoush, Seyed Shahram
Abstract: The effects of six non-starter lactic acid bacteria (NSLAB) as biopreservative agents against mycotoxigenic moulds in fresh cheeses were investigated. The potential of NSLAB to inhibit the growth of contaminating fungi was evaluated using end point (antifungal overlay assay and mycelium inhibition growth) and descriptive (antifungal assay on cell-free cheese extract) methods. The application of all NSLAB except Lactobacillus plantarum KU13 as the sole starter culture of fresh cheese resulted in significant delay of mycelial growth of Aspergillus flavus and Aspergillus parasiticus on the cheese surface. Compared with other NSLAB strains, Lb. plantarum PIN exhibited the most antifungal activity and delayed the mycelia growth of A. flavus and A. parasiticus on the cheese surface by 19 and 22 days, respectively (at 4 °C). The present study indicated that NSLAB could be used as a natural biopreservatives, for controlling the problems caused by mould growth in cheese.